Rapamycin ameliorates the CTLA4‐Ig–mediated defect in CD8+ T cell immunity during gammaherpesvirus infection. Issue 10 (19th May 2015) - Pinelli, D. F.; Wakeman, B. S.; Wagener, M. E.; Speck, S. H.; Ford, M. L.
<x xml:space="preserve">Abstract</x> Latent viral infections are a major concern among immunosuppressed transplant patients. During clinical trials with belatacept, a CTLA4‐Ig fusion protein, patients showed an increased risk of Epstein–Barr virus‐associated posttransplant lymphoproliferative disorder, thought to be due to a deficient primary CD8+ T cell response to the virus. Using a murine model of latent viral infection, we observed that rapamycin treatment alone led to a significant increase in virus‐specific CD8+ T cells, as well as increased functionality of these cells, including the ability to make multiple cytokines, while CTLA4‐Ig treatment alone significantly dampened the response and inhibited the generation of polyfunctional antigen‐specific CD8+ T cells. However, the addition of rapamycin to the CTLA4‐Ig regimen was able to quantitatively and qualitatively restore the antigen‐specific CD8+ T cell response to the virus. This improvement was physiologically relevant, in that CTLA4‐Ig treated animals exhibited a greater viral burden following infection that was reduced to levels observed in untreated immunocompetent animals by the addition of rapamycin. These results reveal that modulation of T cell differentiation though inhibition of mTOR signaling can restore virus‐specific immune competence even in the absence of CD28 costimulation, and have implications for improving protective immunity in transplant recipients.